2021
DOI: 10.1002/iju5.12264
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐tubular penile fracture: A case of complete rupture of urethra and bilateral corpus cavernosa

Abstract: Introduction Tri‐tubular penile fracture is a very rare subset of penile fractures, typically due to high‐energy trauma to the erect penis. Case presentation A 26‐year‐old healthy man presents with a triad of audible crack, immediate detumescence, and hematoma formation, following blunt trauma sustained during vaginal sexual intercourse. A diagnosis of penile fracture is made, with intraoperative finding of a complete traumatic transection of the urethra with total bilateral corpus cavernosa disruption. Both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…3 Young et al reported a case of complete rupture of the urethra and bilateral corpus cavernosa, which could be the most severe type of penile fracture. 4 The gold standard management for penile fractures is immediate surgical repair. 2 The ruptured tunica should be closed with interrupted absorbable sutures via circumcising or a penoscrotal midline incision.…”
Section: Editorial Commentmentioning
confidence: 99%
“…3 Young et al reported a case of complete rupture of the urethra and bilateral corpus cavernosa, which could be the most severe type of penile fracture. 4 The gold standard management for penile fractures is immediate surgical repair. 2 The ruptured tunica should be closed with interrupted absorbable sutures via circumcising or a penoscrotal midline incision.…”
Section: Editorial Commentmentioning
confidence: 99%